2023
DOI: 10.3389/fnins.2023.1192188
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac vagal afferent neurotransmission in health and disease: review and knowledge gaps

Abstract: The meticulous control of cardiac sympathetic and parasympathetic tone regulates all facets of cardiac function. This precise calibration of cardiac efferent innervation is dependent on sensory information that is relayed from the heart to the central nervous system. The vagus nerve, which contains vagal cardiac afferent fibers, carries sensory information to the brainstem. Vagal afferent signaling has been predominantly shown to increase parasympathetic efferent response and vagal tone. However, cardiac vagal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 139 publications
(204 reference statements)
0
4
0
Order By: Relevance
“…37,38 Modulation of the autonomic nervous system by the cardiac afferent reflex represents another mechanism that can mediate the effect of the heart on metabolism. 39–43 This possibility is supported by several studies implicating sympathetic traffic in heart failure–associated cachexia caused by excess loss of adiposity. 44,45 Remarkably, a prospective study identified muscle sympathetic nerve activity as the most sensitive marker of weight loss in heart failure patients.…”
Section: Metabolic Impact Of Cardiovascular Organsmentioning
confidence: 81%
“…37,38 Modulation of the autonomic nervous system by the cardiac afferent reflex represents another mechanism that can mediate the effect of the heart on metabolism. 39–43 This possibility is supported by several studies implicating sympathetic traffic in heart failure–associated cachexia caused by excess loss of adiposity. 44,45 Remarkably, a prospective study identified muscle sympathetic nerve activity as the most sensitive marker of weight loss in heart failure patients.…”
Section: Metabolic Impact Of Cardiovascular Organsmentioning
confidence: 81%
“…We hypothesize that during CPNS therapy, afferent signaling is modulated either directly by direct stimulation of afferent nerve fibers or indirectly by reacting to the low-level CPNS sympathetic stimulation. The CANS controls the sympathetic and parasympathetic outflow based on the afferent/sensory input and therefore afferent modulation could cause a significant change in the whole CANS (Chen et al, 2015 ; van Weperen and Vaseghi, 2023 ).…”
Section: Cardiopulmonary Nerve Stimulationmentioning
confidence: 99%
“…We hypothesize that during CPNS therapy, afferent signaling is modulated either directly by direct stimulation of afferent nerve fibers or indirectly by reacting to the low-level CPNS sympathetic stimulation. The CANS controls the sympathetic and parasympathetic outflow based on the afferent/sensory input and therefore afferent modulation could cause a significant change in the whole CANS (Chen et al, 2015;van Weperen and Vaseghi, 2023).…”
Section: Potential Mechanism Of Actionmentioning
confidence: 99%